Investigation of resistance mechanisms in colistin resistant some enterobacteriaceae in cancer patients in Egypt - Asmaa Abdulhak Elsayed Mohammed Abdelaal; Hadeer Elmahallawy; Magdy Aly Amin; Mai Mahmoud Zafer (Cairo : Asmaa Abdulhak Elsayed Mohammed Abdelaal, 2019)
The recent emergence of plasmid-encoded colistin resistance mechanism (MCR-1and MCR-2) among human enterobacterial isolates presents a threat for the rapid global spread. Colistin resistance is mainly mediated by the alteration in the LPS of bacterial outer membrane; these alterations are mediated by mutations in mgrB gene which is the most commonly reported. This study aimed to investigate the colistin-resistance rates among Klebsiella pneumoniae and Escherichia coli isolates obtained from Cancer patients in Egypt and the possible underlying mechanisms of colistin resistance. Minimum inhibitory concentrations (MICs) to colistin were determined according to the (EUCAST) guidelines. Broth microdilution and and E-tests were used to test colistin susceptibility. PCR and sequencing of mcr-1 and mcr-2 were performed. The mgrB gene was amplified and sequenced. Clonal diversity for colistin resistant K. pneumoniae isolates was evaluated by multilocus sequence typing (MLST). Four hundred and fifty Enterobacteriaceae were included in this study. Forty (8.8%) colistin-resistant isolates including 22 K. pneumoniae and 18 E. coli were detected over 10 months. Fifty % of the colistin resistant isolates were carbapenem resistant (20/40)
Thesis (M.Sc.) - Cairo University - Faculty of Pharmacy - Department of Microbiology and Immunology
Issued also as CD
Keywords: Cancer patients; Colistin resistant; Enterobacteriaceae